Menstrual Hygiene Management Among Adolescent Girls in Selected Secondary Schools in Ahoada, Rivers State - Afoma, Onyenanu Obiageli; Kenneth, Imarenezor Edobor Peter (Darul Yasin Al Sys, 2025)
Menstrual hygiene management (MHM) is a critical public health and educational issue affecting adolescent girls, particularly in low-resource settings. In Ahoada, Rivers State, Nigeria, many adolescent girls face significant challenges in managing menstruation due to limited access to sanitary products, inadequate sanitation facilities, and insufficient knowledge about menstrual health. These challenges contribute to adverse outcomes such as poor self-esteem, emotional distress, increased absenteeism, and diminished academic performance. This study investigated MHM practices among adolescent girls in selected secondary schools in Ahoada, aiming to provide evidence to inform policy and programmatic interventions. A cross-sectional survey design was employed, and data were collected from 300 adolescent girls using a structured questionnaire. The findings revealed that 73% of respondents lacked access to sanitary pads, 60% reported missing school during menstruation, and 67% experienced menstrual-related stigma. Emotional distress or anxiety during menstruation was reported by 70% of participants, while 63% indicated that menstruation negatively impacted their academic performance. Additionally, 27% of the respondents demonstrated inadequate knowledge of menstrual hygiene. The study highlights the pressing need for comprehensive, school-based interventions, including menstrual hygiene education, improved water and sanitation infrastructure, and access to affordable sanitary products. These findings contribute to the limited body of literature on MHM in Rivers State and underscore the importance of addressing menstrual health to support adolescent girls' well-being and educational attainment.